Midnight kiss - Carr, Robyn; Carr, Robyn; Brashear, Jean.; Dahl, Victoria (Don Mills, Ont. : Harlequin, 2010)
Midnight confessions. At a local bar New Year's Eve party in Southern California, two lonely revelers decide that the best balm for their broken hearts might be each other. Midnight surrender. When a flirty woman lawyer with a "bad -boy addiction" meets a nice Irish carpenter on Thanksgiving at her friends' home, she is not expecting the sparks that begin to fly between them. Midnight assignment. Working together over the Christmas and New Year's holidays on a bank takeover is made worse for two federal specialists by an ill-advised kiss that re-ignites a lingering spark between them. What will come next?
Midnight confessions / Robyn Carr -- Midnight surrender / Jean Brashear -- Midnight assignment / Victoria Dahl.
"Harlequin anthology." -- Cover, p.[4]
Keywords: New Year -- Fiction; Man-woman relationships -- Fiction; Holidays -- Fiction; Love stories